15 plus -3 equals 12 12 divided by -6 equals -2
18
1 Becuase division comes before addition. so 12/4=3 and -2 plus 3 is 1.
10+2÷(4x3)= 10+2÷ (12)= 12÷(12)= 1
-9
12 divided by 4 plus 2 times 3 = 9
15 plus -3 equals 12 12 divided by -6 equals -2
2/3 divided by 4/9 plus 1/2 2/3 times 9/4 = 18/12 + 6/12 = 24/12 = 2
11
18
1 Becuase division comes before addition. so 12/4=3 and -2 plus 3 is 1.
10+2÷(4x3)= 10+2÷ (12)= 12÷(12)= 1
What is 100 divided by 2 plus 3
3 divided by 4 plus 1 divided by 2 minus 2 divided by 3
45 ÷ 15 ÷ 3 + 2 = 3
10 + 12/3 + 20 = 34
-9